2003
DOI: 10.1023/a:1023386122344
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Our findings support the common opinion that war and terror incidents severely hurt children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…We translated the relevant information into English. Overall, ten studies [26, 31, 40, 45, 47, 51, 58, 68, 70, 73] reported mean and standard deviation for relevant outcomes. These results are presented in Additional Material 2.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We translated the relevant information into English. Overall, ten studies [26, 31, 40, 45, 47, 51, 58, 68, 70, 73] reported mean and standard deviation for relevant outcomes. These results are presented in Additional Material 2.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Reasons for unclear risk of bias ratings were mainly because the sample was a convenience sample, the sample size was not justified and rather small, or the survey’s response rate was not reported. Sixteen studies showed high risk of bias [29, 32, 52, 55, 5860, 63, 65, 67, 69–74], because of low response rates (< 30%), inconsistent results, or the lack of informed consent or ethical approval (as rated by the AXIS tool).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have suggested a relationship between older age and psychiatric problems, while others have indicated a reverse association and others did not present any association at all. 20 23 Age at onset of events, age at initiation of the migration process, the status of educational rights appropriate to age where the refugees have resided in, legal regulations, and parental loss are among factors that may be associated with such discrepancies. In our study, we found a higher rate of psychiatric disorders among children who were older, consistent with reports in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found a higher rate of psychiatric disorders among children who were older, consistent with reports in the literature. 23 26 This may be associated with various factors, such as long-term problems in the countries from which refugees originated. It is possible that older children experienced many traumatic events prior to migration, during the process, and after the process, which may have affected their psychosocial development.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the development of the revised BDI-II 20 years ago (BDI-II; Beck et al, 1996 ), the original BDI is still widely used in clinical and research settings in both North America (Foa et al, 2005 ; Gillespie et al, 2009 ; Veerman et al, 2009 ; Delisle et al, 2012 ; Jayawickreme et al, 2014 ; Udo et al, 2015 ) and Europe (e.g., Suija et al, 2012 ; Lahlou-Laforet et al, 2015 ; Wardenaar et al, 2015 ). Strikingly, the BDI continues to be widely used to assess for depression in refugees and internally displaced and war-impacted populations (Mghir and Raskin, 1999 ; Bhui et al, 2003 ; Ghazinour et al, 2003 ; Yurtbay et al, 2003 ; Basishvili et al, 2012 ; Luitel et al, 2013 ; Kuittinen et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%